COMPARATIVE STUDY OF COMPLETED SUICIDE BASED ON SEASON AND DISEASES IN BUSHEHR PROVINCE, (2006-2015) - Mahmood, Montazeri; Hosseini, Hiyam; Jokar, Behroz (International Journal of Research -GRANTHAALAYAH, 2017)
Suicide, an act in which individuals sacrifice voluntarily themselves, is considered as a serious psychosocial problem. The main objective of the present study was to determine the comparative study of completed suicide based on season and diseases in Bushehr during 2006-2015. This consideration has been done as a retrospective cross-sectional study; the data were collected by the check list. After coordination to the medico legal 343 cases of completed suicide lead to death over a ten year period from 2006 to 2015 were extracted and the data were analyses by SPSS software. Completed suicides were most prevalent in spring 29.7% (102), whereas least prevalent in autumn 20.1% (69). There was no significantly in different seasons in year (P=0.065). But, was a statistically significant difference observed in the different gender and different seasons of the year (P=0.001). The maximum number of completed suicides 10.2% (35) was observed in April, while the minimum number 6.1% (21) was reported in September and October, too. The value Chi square test was statistically significant differences diseases and different seasons (P=0. 001). The psychological disease was observed most in spring and winter seasons. Also was a significant relationship between season of the year and the method of suicide (P=0.001). The number of completed suicides was higher in moderate and cold seasons.